Fire-Proneness as a Prerequisite for the Evolution of Fire-Adapted Traits - Lamont, Byron; He, Tianhua (Elsevier, 2017)
Fire as a major evolutionary force has been disputed because it is considered to lack supporting evidence. If a trait has evolved in response to selection by fire then the environment of the plant must have been fire-prone before the appearance of that trait. Using outcomes of trait assignments applied to molecular phylogenies for fire-stimulated flowering, seed-release, and germination, in this Opinion article we show that fire-proneness precedes, or rarely coincides with, the evolution of these fire-adapted traits. In addition, fire remains central to understanding germination promoted by smoke among species occurring in non-fire-prone environments because of the historical association of their clade with fire. Fire-mimicking selection and associated exaptations have no place in understanding the evolution of fire-adapted traits because we find no support for any reversal in the fire-trait sequence through time. Ancestral trait reconstruction using accurately dated molecular phylogenies is revolutionizing our understanding of fire-directed evolution among plants.Ancestral fire-prone lineages may also be identified on molecular phylogenies using fossil charcoal and reconstruction techniques.Ascertaining whether or not the onset of exposure to fire preceded the advent of putatively fire-adapted traits enables the identification of unique adaptations to fire.Fire-mimicking (multi-agent) selection and associated exaptations are alternative explanations of apparent fire-adapted traits that require selection via drought or non-unique components of fire to precede selection by fire.Smoke-stimulated germination among plants in non-fire-prone habitats may not be an anomaly if it can be shown that they possess a dormant gene mechanism inherited from a fire-prone past.